THE SCHOLAR’S CONTRIBUTIONS OF THE LOCALITY AL-HARBIYA OF THE INTELLECTUAL LIFE IN THE THIRD ABBASID ERA - Mohammed Najim Abd Al-Shaybany (Scholar Express Journal, 2021)
This research was devoted to the study of the contributions of the scholars of the Baghdadi Al-Harbiya locality in the intellectual life of the Third Abbasid era (334-447 AH/945-1055AD), and the intellectual products that contributed to the prosperity of the intellectual movement in the city of Baghdad at that time, which made it a shining city in the sky of Arab-Islamic civilization, intended by students of science and lovers of knowledge from all parts of the world to obtain science and knowledge, therefore the research came as required by the nature of the study it is divided into two axes, the first axis is concerned with studying the nature of Al-Harbiya locality and the second axis specialized in studying the scientific contributions of the scientists of AlHarbiya locality, and we concluded through this research that the scientists of Al-Harbiya locality had many scientific contributions in the intellectual life of the Abbasid era, Especially in the field of their development of many sciences and their contribution to the scientific activities of that era by providing them to the Arab Library with many scientific and cultural literature
Keywords: Scholars of the locality of Al-Harbiya; the locality of Al-Harbiya Baghdadi; the intellectuals of the locality of Al-Harbiya